Hidden Treasures in Theological Education: The Writing Tutor, the Spiritual Director, and Practices of Academic and Spiritual Mentoring - Yaghjian, Lucretia B. (Teaching theology and religion, 2013)
Mentoring is an important but often overlooked resource in theological education and students' academic and spiritual formation. This essay profiles the mentoring practices and postures of the writing tutor and the spiritual director as exemplars of academic and spiritual mentoring. An extended probe of this analogy affirms the integration of academic and spiritual formation as a core value in theological education; identifies mentoring in theological education as a hidden treasure fostering this integration and warranting attention as a theological practice; and re-envisions the theological practice of mentoring under the traditional rubric of the “care of souls,” embracing the relational, educational, formational, spiritual, and rhetorical dimensions of this practice.